Issues for routing in the optical layer. - Strand, J. (IEEE Communications magazine)
Optical layer control planes based on MPLS and other Internet protocols hold great promise because of their proven scalability, ability to support rapid provisioning, and auto discovery and self-inventory capabilities and are under intense study in various standards bodies. To date however little attention has been paid to aspects of the optical layer which differ from those found in data networking. We study three such aspects which impact routing: network elements which are reconfigurable, but in constrained ways; transmission impairments which may make some routes unusable; and diversity. We conclude that if emerging optical technology is to be maximally exploited, heterogeneous technologies with dissimilar routing constraints are likely. Four alternative architectures for dealing with this eventuality are identified and some trade-offs between centralizing or distributing some aspects of routing are discussed